New or otherwise interesting Lichens. VI, including a lichenicolous fungus - Kalb, Klaus; Buaruang, Kawinnat; Mongkolsuk, Pachara; Boonpragob, Kansri (Phytotaxa, 2012)
Eight lichenized ascomycetes and one lichenicolous non-lichenized fungus are described as new to science, namely Coniocarpon coralloideum from Venezuela and Ecuador, Crustospathula khaoyaiana from Thailand, Cryptolechia pittieriana from Venezuela, Cryptothecia napoensis from Ecuador, Malmidea incrassata from Brazil, Malmidea reunionis from Réunion, Malmidea tratiana from Thailand, Stirtonia rhizophorae from Thailand and the nonlichenized fungus Melaspilea lekae from Thailand. The following ten taxa are new additions to the lichen biota of the countries given in brackets: Agonimia pacifica (China), Bactrospora myriadea (Thailand), Brigantiaea phaeomma (China), Brigantiaea sorediata (Tanzania), Coenogonium pineti (Thailand), Cratiria vioxanthina (Brazil), Cryptothecia eungellae (Thailand), Eschatogonia dissecta (Brazil), Malmidea badimioides (Mexico) and Porpidia albocaerulescens var. polycarpiza (Thailand). Buellia vioxanthina is transferred to the genus Cratiria, and a new chemotype of Eschatogonia prolifera was found in Thailand.